Factors Influencing the Purchase Intention Towards Electronic Vehicle and Impact on Individual’s Pro-Environmental Future Intentions (Journal of Asian Development Studies, 2024)
This study explores the key determinants influencing consumer purchase intention toward electric vehicles (EVs) and their role in promoting pro-environmental behavior. In light of increasing climate concerns and sustainability goals, understanding the behavioral and technological factors that drive EV adoption is crucial, particularly in emerging economies. The research integrates the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Theory of Planned Behavior (TPB) to examine performance expectancy, effort expectancy, social influence, facilitating conditions, and environmental concern. A quantitative approach using survey data from 400+ respondents was analyzed via PLS-SEM and regression techniques. Results show that environmental concern is the most significant predictor of EV purchase intention, followed by performance expectancy. Surprisingly, social influence had no meaningful effect, challenging traditional views on peer-driven technology adoption. Facilitating conditions and effort expectancy had a moderate impact. The study provides valuable insights for policymakers, marketers, and sustainability advocates, highlighting the importance of environmental awareness over social cues in driving EV adoption. This research contributes to the theoretical advancement of green consumer behavior and offers strategic recommendations for increasing EV penetration. Future research should explore the moderating role of financial incentives and government policy in shaping EV-related decisions.